Simultaneous operation by the minilaparotomy approach in the presence of acute gangrenous calculous cholecystitis and hepatic hemangioma - A. V. Kapshitar (Patologìâ)
According to domestic surgeons the simultaneous operations (SO) in biliary surgery are carried out most often. Practical surgeons refer to performance of SO in the presence of acute cholecystitis (AC) reservedly enough. From all the patients with cholelithiasis SO are carried out in patients with AC in 6,9-30%. Postoperative complications are registered in 0,2-23,9% of patients, and lethal outcomes – in 2-20%. In structure of benign tumors of the liver hemangioma of the liver (LG) is found in 30-50% of patients. We didn't find messages about simultaneous excision of LG and a gall bladder in the patients with acute gangrenous calculous cholecystitis by the minilaparotomy approach.